Annual Variation in Soil Enzyme Activity in a Paddy Field: Soil Temperature and Nutrient Availability Are Important for Controlling Enzyme Activities. (10th October 2018) - Kunito, Takashi; Shiroma, Takashi; Moro, Hitoshi; Sumi, Hirotaka
Abstract : Annual variations in enzyme activities involved in carbon (C), nitrogen (N), phosphorus (P), and sulfur (S) cycling and soil physicochemical properties were examined in a Japanese paddy field. All the enzyme activities determined at the field soil temperature (range, 2.2°C–28.3°C) increased exponentially with soil temperature (p < 0.001 ). Significant negative correlations were found between Bray-2P concentration and the ratio of acid phosphatase to β -D-glucosidase activity (Spearman r = −0.631, p = 0.005) and between total N and the ratio of L-asparaginase to β -D-glucosidase activity ( r = −0.612, p = 0.007 ), suggesting that in accordance with the resource allocation model, acid phosphatase and L-asparaginase were synthesized by microorganisms depending on the temporal changes in soil P and N availability. These results suggest the significance of soil temperature in controlling in situ enzyme activities in paddy soil and also that the stoichiometry of enzyme activities associated with C, N, and P acquisition reflects the soil nutrient availability.